Pro spring integration - Lui, Mark (Apress, 2011)
Pro Spring Integration is an authoritative book from the experts that guides you through the vast world of enterprise application integration (EAI) and application of the Spring Integration framework towards solving integration problems. The book is:  An introduction to the concepts of enterprise application integration A reference on building event-driven applications using Spring Integration A guide to solving common integration problems using Spring Integration What makes this book unique is its coverage of contemporary technologies and real-world information, with a focus on common problems that users are likely to confront. This book zeroes in on extending the Spring Integration framework to meet your custom integration demands. As Spring Integration is an extension of the Spring programming model, it builds on the Spring Framework's existing support for enterprise integration. This book will take you through all aspects of this relationship and show you how to get the most out of your Spring applications, where integration is a consideration. It discusses simple messaging within Spring-based applications and integration with external systems via simple adapters. Those adapters provide a higher-level of abstraction over Spring's support for remoting, messaging, and scheduling, all of which receives coverage in this book.